智歯抜歯を行った再発性多発軟骨炎患者の1例 - 外山, 直人; 石川, 純; 南部, 和也; 鈴木, 秀祐; 藤本, 雄大; 井出, 貴洋 (日本口腔外科学会雑誌, 2024)
Relapsing polychondritis (RP) is a rare chronic inflammatory disease specific to cartilage tissue. Treatment of RP is aimed at preventing destruction of the cartilage tissue and involves the use of multiple immunosuppressive drugs. Postoperative infection should be considered in cases of RP because infection is a trigger for disease relapse. A 28-year-old man was referred to our department for extraction of the third molars in June 2022. The patient was diagnosed with RP in September 2009. He was taking multiple immunosuppressive drugs. The clinical diagnosis was carious third molars with pericoronitis. He was hospitalized for the extractions in July 2022. Prophylactic antimicrobials were administered without discontinuation of regular medication and tooth extraction was performed. The patient was monitored for signs of RP relapse during the follow-up. At 21 days postoperatively, no signs of infection or RP relapse were observed; further, epithelialization was confirmed and the patient was doing well.